“Amante não tem lar” – análise das relações entre o feminejo e a dominação masculina - Melo, Ana Flávia Tavares de (2021)
This work investigated and analyzed the participation of women in the universe of country music and, more specifically, in the women's movement and the possible relationships with male domina tion, to discuss and reflect on the problem expressed by the question: the women's movement con tributes to new forms of women's participation in the universe of country music and/or strengthens male domination relationships, that is, would this be a space for overcoming and/or legitimizing this process? In this way, a historical overview from the colonization process and the arrival of the viola in Brazil was elaborated based on theoretical reference Freyre (2006), Holanda (2014), Tinhorão (2010), and Vilela (2017), for understanding that they significantly contribute to the presentation of this brief history, avoiding possible anachronisms in the presence of women in this process. A study of the universe of country music was carried out, supported by scholars of this theme, such as Alonso (2015); Antunes (2012); Caldas (1987), and Nepomuceno (1999), to understand the elements that contributed to the construction of the female movement. In this path, the work sought to highlight the pioneering social agents in each era of the country music scene and how they contributed to the dynamics in this social space. Finally, the current outline of the women's movement was evidenced. Both the historical trajectory and the data analysis were orchestrated by the theory of knowledge of the French sociologist Pierre Bourdieu (2019) through the book Male domination, which contributed to the understanding of the mechanisms inherent in a process of male domination. In this sense, after analyzing and discussing the data – which were captured through the lyrics and interviews given by pioneer female composers and singers Maiara and Maraísa; Marília Mendonça; Simone e Simaria and Naiara Azevedo – it was possible to verify that the women's movement, already in its origins, in 2014, had marked traces of male domination, and there were no significant changes over the course of 7 years. It is considered that there may have been changes in the forms of dissimulation of male domination devices. It concludes that, in addition to legitimizing, the women's movement also col laborates to disseminate the processes of male domination.